Adsorption of a hydrophobic cationic polypeptide onto acidic lipid membrane. (28th July 2017) - Duan, Xiaozheng; Zhang, Ran; Ding, Mingming; Huang, Qingrong; Xu, Wen-Sheng; Shi, Tongfei; An, Lijia
Abstract: We study the interactions between a cationic polypeptide chain with tunable hydrophobicity and a fluid phosphatidyl-choline lipid monolayer composed of neutral, tetravalent phosphatidylinositol 4, 5-bisphosphate and univalent phosphatidylserine acidic lipids at various ionic concentrations of the salt solution, using a simple coarse-grained Monte Carlo model. Our work illustrates that the enhancement in the polypeptide hydrophobicity strengthens the short-range attractions between monomers, which elevates the electrostatic energy gain of the polypeptide/membrane complexity, but enlarges the conformational entropy loss of the shrunken polypeptide and demixing entropy loss of the segregated acidic lipids. These energy-entropy competitions result in qualitatively different dependences of anchoring/dissociation transition critical ionic concentration on hydrophobic monomer-monomer energy parameter ε h for polypeptides with short and long chain lengths. In the anchoring region, we show that changing the polypeptide hydrophobicity leads to diverse chain conformations at various ionic concentrations for polypeptides with both short and long chain lengths. Furthermore, we illustrate the non-trivial feature of the reorganization of the acidic lipids underneath the anchored polypeptides. Our work demonstrates that the chain conformations of the anchored polypeptides with different hydrophobicities can be a key factor influencing the amounts and concentration gradients of the segregated acidic lipids. These findings suggest that polypeptide hydrophobicity provides an efficient molecular factor for tailoring the anchoring/association transition and interfacial structures of the polypeptide/membrane complexities, thereby offering insight into the innovation of new biotechnologies based on the functional switch of the anchored biopolymers and the regulation of messenger lipids. Graphical abstract: Highlights: We study the interactions between a cationic polypeptide chain with tunable hydrophobicity and a fluid anionic lipid monolayer at various ionic concentrations, using a simple Monte Carlo model. Our findings suggest that polypeptide hydrophobicity provides an efficient molecular factor for tailoring the anchoring/association transition and interfacial structure of the polypeptide/membrane complexities. Our work offers insight into the innovation of new biotechnologies based on the regulation of messenger lipids.